Concurrent cases of bilateral anterior shoulder dislocation: our observations in three cases - Akinci, Orhan; Akalin, Yavuz; Otuzbir, Ali; Oztürk, Alpaslan (The European Research Journal, 2016)
Bilateral anterior shoulder dislocations are rarely seen and usually occur due to the same mechanism arising from traumatic injuries. In here, we discussed three cases of traumatic bilateral anterior shoulder dislocation , one had an additional patella fracture, and the other one had bilateral tuberculum majus fracture. All of the patients were female and our first case that presented here was 65-year-old and given a closed reduction for isolated bilateral anterior shoulder dislocation that occurred as a result of falling due to an epileptic seizure. The second patient was 70-year-old and had bilateral shoulder dislocation and patella fracture (right leg) after of falling down the stairs due to syncope. Closed reduction was applied to the bilateral shoulder dislocation. Patella fracture on the right leg was fixated using open reduction internal fixation method. The third patient, who was 57-year-old, fell down from the stairs and had bilateral anterior shoulder dislocation accompanied by bilateral tuberculum majus fracture, and she was given closed reduction. For all three of the cases, Hippocrates method was used as the closed reduction method.